Biogeochemical patterns during cold-water coral growth and their potential application for environmental interpretation - Oppelt, Alexandra (Trinity College (Dublin, Ireland). Department of Geography, 2016)
In the light of changing marine environments as a consequence of climatic shifts it is essential to gain a better understanding of such vulnerable habitats especially when they are located out of sight in the deep sea. The aragonitic skeletons of colonial scleractinian cold-water corals offer a unique opportunity to learn more about remote ocean areas and climate-driving current systems. A detailed study on biomineralisation to decode the information in these CaCOa-based recording units is therefore essential. A selection of three scleractinian species most common above 1,000 m depth in the NE Atlantic was studied here to deliver additional insight and new tools to extent our understanding. The presented thesis successfully applied major, minor and trace element analysis to show variations in the geochemical composition of coral skeletons in association with microstructure and growth. This correlation and association is shown in detail for the aragonitic skeletons of scleractinian species Lophelia pertusa and Madrepora oculata. The study highlights small-scale variations in geochemical composition in association with microstructures along the precipitation of a complete Lophelia pertusa theca combining two dimensions of growth.
Keywords: Geography, Ph.D.; PhD Trinity College Dublin, 2016